a Evaluation of Primary Service Readiness in Handling Catastrophic Disease Emergencies in Rural Areas: Evaluation of Primary Service Readiness in Handling Catastrophic Disease Emergencies in Rural Areas - Floriana, Callina (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Evaluation of Primary Service Readiness in Handling Catastrophic Disease Emergencies in Rural Areas